TRANSFUSI DARAH DALAM TIMBANGAN FIKIH: Antara Najis dan Maslahah Perspektif Kaidah al-Ḍarar Yuzāl - Achmad Fageh; Heny Lutfiana Hamdi (Universitas Islam Lamongan, 2021)
Blood transfusions are a new problem in Islamic law discourse. In the context of Jurisprudence studies, blood includes unclean objects material (lidzatihi). And there is no syar'i law that explicitly addresses the practice of blood transfusions. This confuses Muslim life. Risks and also benefits arising from the practice of blood transfusions both, from donors and recipients of blood donations (recipient) need to be considered by both. The purpose of this is to save the lives of the recipient either, because of accidents or diseases. The unlawful legal status of the use of blood becomes mandatory when faced with urgent needs, at a time when blood transfusions are the only way to save a person's life. In this case, it is based on the fourth principle Fiqhiyyah rule which is: al-Ḍarar Yuza>l (الضَّرَرُ يُزَالُ) that the danger must be eliminated/prevented. So the practice of blood donation is a thing that must be done to avoid greater harm, for example, it will lose lives if it does not immediately make a blood donation. Also, it is revealed in a hadith narrated by Ibn Majah from Ibn 'Abbas, لَا ضَرَرَ وَلَا ضِرَر (not to fade and should not be harmed). Therefore, in practice, blood transfusions need to have adhered to the procedural requirements of the health program to donors and recipients so as not only to eliminate the danger of recipients but also avoid harm to the donor.